EMERGENCY PREPAREDNESS PLANNING AND ITS EFFECT ON LANDSLIDE DISASTER READINESS: A COMMUNITY-BASED STUDY - Widayati, Dhina; Rachmania, Diana; Almira Hutami, Nur; Mukhtar, Madiha (Universitas Airlangga, 2025)
ABSTRACT The problem of landslide risk that has a significant impact and the importance of preparedness efforts, it is very necessary to increase public awareness and perception to participate in landslide disaster planning. The public must understand the emergency plan to overcome the risk of landslides that can threaten safety, so it is necessary to provide an Emergency Planning simulation. This study was intended to explore the effect of emergency preparedness planning on community’s ability to prepare for and respond to landslide disasters. This research with Preexperimental design involved 84 respondents as the sample size through purposive sampling technique with inclusion criteria of youth groups aged 17-35 years. In this study, Emergency Planning simulation intervention was given twice with a duration of 170 minutes for each face-to-face meeting. The results showed an increase in community preparedness in the good category, which initially increased from 33.3% to 53.5% and a decrease in the less prepared category from 14.3% to 3.6%. The results of the Wilcoxon test data analysis obtained P value: 0.001 (<a: 0.05) indicating an influence of emergency preparedness planning on community’s ability to prepare for and respond to landslide disasters. Emergency planning is very important to be known and implemented by the community to be better prepared to face landslide-prone emergencies. Emergency planning simulation can increase public knowledge and awareness of the importance of preparedness in facing landslides, so as to minimize the number of victims and losses that will be experienced. It is recommended that the application of Emergency planning can be expanded to the entire community so as to increase joint preparedness Keywords; youth groups; simulation; emergency planning;readiness.